NEOPTERIN DAN PEROKSIDA SERUM SEBAGAI PETANDA MAKROFAG TERAKTIVASI PADA TUBERKULOSIS PARU AKTIF DAN INDIVIDU BERKEBAHAYAAN TINGGI (Serum Neopterin and Peroxide As Marker of Activated Macrophages on Active Pulmonary Tuberculosis and Individuals At High Risk) - I Nyoman Wande; Ni Made Linawati; I Made Bagiada; IWP. Sutirta Yasa; AAN. Subawa (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Failure of macrophages to phagocytize Mycobacterium tuberculosis causes the release of hydrogen peroxide/peroxide (H2O2) bythe activated macrophages. Neopterin is one of the most important markers in the activated macrophages. Neopterin is a pteridinederivative produced by the activated macrophages through the stimulation of interferon gamma. Increased levels of Neopterin has beenreported in lung tuberculosis. Activation of macrophages is essential to the development of tuberculosis infection that can lead to activepulmonary tuberculosis or latent tuberculosis, in this case is a high-risk for healthy individuals. To determine the differences in serumlevels of Neopterin and H2O2 between patients with active pulmonary tuberculosis and healthy individuals at high risk of pulmonarytuberculosis. A total of 15 patients with active pulmonary tuberculosis and 15 healthy individuals at high risk examination serumNeopterin levels and peroxide (H2O2). Active pulmonary tuberculosis patients when the results of sputum smear examination chest x-raysis obtained positive results. Healthy individuals at high risk when the results of smear examination and chest x-rays is negative. Thelevel of Neopterin was examined using a double antibody sandwich immunoassay with Human neopterin (NEOP) ELISA Kit ® BioassayTechnology Laboratory. The level of peroxide was examined using quantitative colorimetric peroxidedetermination with QuantiChromTMPeroxide Assay Kit (DIOX-250)®. Neopterin serum levels between patients with active pulmonary tuberculosis and healthy individualsat high-risk were analysed by independent samples t-test. H2O2 serum levels between patients with active pulmonary tuberculosis andhealthy individuals at high-risk were analysed with Mann Whitney Test. The confidence level is p <0.05. The mean Neopterin levelsin patients with active pulmonary tuberculosis was 5.17±4.64 nmol/L, the mean Neopterin levels in group of healthy individuals athigh risk was 3.97±1.79 nmol/L. Statistical analysis by the independent samples t-test found no significant differences between groupsin Neopterin serum levels of patients with active pulmonary tuberculosis and healthy individuals at high risk (p=0.357). The meanserum levels of H2O2 of group of patients with active pulmonary tuberculosis was 26.38±3.00 μM, the mean levels of H2O2of group ofhealthy individuals at high risk of 20.69±4.46 μM. Statistical analysis with non-parametric Mann-Whitney Test was found significantdifference in the peroxide (H2O2) levels between groups of patients with active pulmonary tuberculosis and group of healthy individualat high-risk (p=0.000). The levels of Neopterin in patients with active pulmonary tuberculosis was not significantly higher comparedto the healthy individuals of high risk. Levels of peroxide (H2O2) serum in patients with active pulmonary tuberculosis was significantlyhigher compared to the group of healthy individuals at high risk. This shows that there is increased activity of macrophages in patientswith active pulmonary tuberculosis, but not effective in eliminating of Mycobacterium tuberculosis.